Repellency of Essential Oils and Plant-Derived Compounds Against Aedes aegypti Mosquitoes - April D. Lopez; Sophie Whyms; Hailey A. Luker; Claudia J. Galvan; F. Omar Holguin; Immo A. Hansen (Insects)
Plant-based oils have a long history of use as insect repellents. In an earlier study, we showed that in a 10% concentration, geraniol, 2-phenylethl propionate, and the plant-based essential oils clove and cinnamon effectively protected from mosquito bites for over 60 min. To expand on this study, we reanalyzed our GC–MS data to identify the short organic constituents of these oils. We then used an arm-in-cage assay to test the repellency of different concentrations and combinations of these oils and pure compounds. We found a sigmoidal relationship between the complete protection time from mosquito bites and the concentration of these oils. The complete protection times we recorded for combinations of these oils suggest an absence of additive effects. The results of this study can inform the development of novel, effective, and plant-based insect repellents.